Perancangan Sistem Persediaan Barang Menggunakan Metode Agile - Nurwahyuni (Swarnadwipa, 2024)
The inventory system is an important mechanism in managing the stock of goods of a company. This system aims to ensure the availability of goods in accordance with customer demand, while optimizing capital expenditure. The design of the inventory system is a crucial stage in optimizing the company's operations. This process involves identifying inventory needs, selecting appropriate inventory management methods, and implementing efficient systems. Designing an inventory system using an agile approach is an innovative step in ensuring the flexibility and responsiveness of the system to market changes and customer needs. The results of blackbox testing show that the inventory system has passed a series of functionality, performance, security, integration, and error tests with test results of 100% in accordance with the functions of the application that has been created. However, regular follow-up monitoring and testing is still required to ensure the system continues to function properly and meet user needs consistently.